Trajetórias de formação e atuação docente na educação infantil do campo: narrativas dos egressos dos cursos magistério e pedagogia da terra – MST - Vieira, Marle Aparecida Fidéles de Oliveira (2023)
This thesis focuses on the training journeys and teaching activities of educators who work with children in Rural Childhood Education (EIC). Its general target is to understand the formative trajectories in the formation and teaching activities of educators who participated in the training courses offered by Magistério e Pedagogia da Terra coordinated by the Landless Rural Workers Movement (MST) in ES, specially educators who work with children in Early Childhood Education (ECE) in agrarian reform settlements. It argues, in this context, that the courses are a claim conquered by the social movement, demarcated by trajectories of performance in teaching, and that they have strengthened the struggle for Field Education (EC). Anchored on Freirian and Bakhtinian theoretical and methodological assumptions, it develops, from the perspective of a qualitative approach, narrative research, sustained on the life stories – both individual and collective ones- of the researched subjects. It uses a questionnaire, semistructured interviews, writing pedagogical letters to the MST, and field diary entries. The analyses carried out allow me to state that the courses claimed by the MST enabled the subjects involved to have access to higher education through teaching in the Agrarian Reform settlements, corroborating the Movement's primary objective of training its educators to work with its social base. They also show that EIC educators understand the importance of being part of MST and the contribution of the course to their lives and to the work they do with the children. The educators recognize the need for more pedagogical support and better investment in infrastructure by the municipalities and ask the Education Sector (SE) to place more emphasis on the training of those who work in this stage of basic education. They highlight the need for a closer relationship between SE and the municipalities of Espírito Santo state in an attempt to help build training processes, given the specificity of the countryside and the children who live there. Data reaffirm the relevance of CE, the training of educators and the children's right to EI.